2011
DOI: 10.1021/ja205773a
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Ion Current Rectification in Conical-Shaped Glass Nanopores

Abstract: Ion current rectification that occurs in conical-shaped glass nanopores in low ionic strength solutions is shown to be dependent on the rate of pressure-driven electrolyte flow through the nanopore, decreasing with increasing flow rate. The dependence of the i-V response on pressure is due to the disruption of cation and anion distributions at equilibrium within the nanopore. Because the flow rate is proportional to the third power of the nanopore orifice radius, the pressure-driven flow can eliminate rectific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
225
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(250 citation statements)
references
References 37 publications
23
225
2
Order By: Relevance
“…1c), consistent with the rectification behavior observed in negatively charged conical geometries. [28][29][30][31] The nanopipettes were filled with (5 kbp or 10 kbp) double-stranded DNA solution and Ag/AgCl electrodes were fitted both in the nanopipette (patch electrode) and in the external reservoir containing only buffer (bath/ground electrode). Under these conditions, the negatively charged DNA molecules inside the nanopipette migrate toward the inner electrode under positive applied potentials and toward the tip of the nanopipette under negative potentials.…”
Section: Resultsmentioning
confidence: 99%
“…1c), consistent with the rectification behavior observed in negatively charged conical geometries. [28][29][30][31] The nanopipettes were filled with (5 kbp or 10 kbp) double-stranded DNA solution and Ag/AgCl electrodes were fitted both in the nanopipette (patch electrode) and in the external reservoir containing only buffer (bath/ground electrode). Under these conditions, the negatively charged DNA molecules inside the nanopipette migrate toward the inner electrode under positive applied potentials and toward the tip of the nanopipette under negative potentials.…”
Section: Resultsmentioning
confidence: 99%
“…Nanofluidic devices have been attracting great interest owing to the unique ionic transport properties, [1][2][3][4] such as ionic selectivity, [5][6][7][8] ionic rectification, [9][10][11][12] local ion depletion/enrichment, [13][14][15][16][17] etc. Of these, electrostatic interactions between ionic species and surface charge of channel play important roles because the electrical double layer (EDL), which can extend as far as 100 nm to only a few angstroms, occupies a non-negligible fraction of nanofluidic channel.…”
mentioning
confidence: 99%
“…It has been reported that nanopores with radii of 200 nm rectified the current based on the gas pressure, 24,46 Figure 5 CO2 activation of ion current rectification in nanochannels Y Xu et al whereas the geometrical structure of the nanopores with radii less than~30 nm will have a negligible effect on the current. Thus, the possible mechanism of the physical gas pressures induced by CO 2 can be excluded for our smart chemical-driven nanopores because the radii of the nanopores in our system are o30 nm (Supplementary Figure S12).…”
Section: Co2 Activation Of Ion Current Rectification In Nanochannelsmentioning
confidence: 98%
“…Nevertheless, most previous studies on rectification have been based on liquid-solid interactions. [18][19][20][21][22][23] The gas phase in the nanofluidic system was not recognized until it was reported in 2011 that the physical loading of gas pressure also influences the rectification property of the nanofluidic system, 24 although this work considered physically driven rectification, and it is hard to distinguish the components of the gas.…”
Section: Introductionmentioning
confidence: 99%